Skills in Guinea : Supply and Demand - World Bank Group (World Bank, Washington, DC, 2017)
In Guinea, the quality of human capital is as crucial for economic success as its vast mineral resources. Improving the quality of education, ensuring the creation of a productive labor with high returns, and, above all, encouraging the creation of private enterprises through a favorable business climate are all essential to boosting productivity and skills. Today, traditional civil service opportunities available are insufficient to absorb ever-growing numbers of Guinean graduates. University enrollments have increased tenfold over the past 10 years, reaching more than 95,000 students in 2012. Graduates between the ages of 25 and 35 face an unemployment rate close to 30 percent, posing a threat to social stability. Education remains disconnected from work, and students are not distributed among academic disciplines according to any economic logic. Technical and vocational training is underdeveloped relative to the needs of industry, namely mining, construction, and agriculture in particular. Companies hire mainly through personal connections, creating a system in which, for all sectors but agriculture, the majority of employee’s report obtaining their jobs through acquaintances. Even in the formal economy, firms recruit predominantly via informal networks. The lack of transport infrastructure and weak electrical power grid, coupled with a poorly developed financial system and challenging institutional environment hinder both the creation of new businesses and growth of existing businesses. Growth projections are encouraging, although not as high as expected due to the Ebola virus disease, and demand for skilled labor is now a national priority. Maximizing the outputs of these new jobs will require strengthening the linkages between higher education (including technical and vocational education and training (TVET)) and high-growth sectors. In this note, we review the current state of education and workforce skills in Guinea. With the support of the new employer-employee survey prepared under this technical assistance and household surveys covering years 2007 and 2012, the note will identify the key bottlenecks faced by firms in hiring qualified workers. The note will conclude by providing recommendations to improve workforce quality.